Effect of pyrolytic carbon addition on the structural and optical properties of TiO2 composite thin films - Katarzyna Wojtasik; Michał Wojtasik; Katarzyna Suchanek; Magdalena Zięba; Paweł Karasiński; Wojciech Pakieła; Grażyna Żak; Wojciech Krasodomski (Scientific Reports)
Abstract The article deals with the preparation and characterization of titanium dioxide thin films containing pyrolytic carbon as potential UV protection films for photovoltaic devices. The carbon used as an additive was obtained by pyrolysis of methane, the main product of which is turquoise hydrogen, and the carbon is a by-product of the process. The resulting carbon material was characterized by Raman spectroscopy, scanning electron microscopy and energy dispersive spectroscopy. Titanium dioxide/pyrolytic carbon composite thin films were prepared by sol-gel method, followed by dip-coating technique. The sols were examined using the dynamic light scattering method. The optical properties of the composite films, including transmittance, reflectance, energy band gap, Urbach energy, porosity, along with their surface morphology and resistance to UV degradation, were evaluated. The results indicate that incorporation of pyrolytic carbon improves the optical properties of composite thin films compared to the samples without carbon, leading to an increase of about 5% in transmittance in the visible range of spectrum. Microscopic observations confirm the presence of pyrolytic carbon in the films, and surface smoothing is noticeable at higher carbon concentrations. These findings suggest the potential use of composite films as UV-blocking films.